2015
DOI: 10.1186/s40623-015-0368-y
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and petrology of lunar meteorite Northwest Africa 2977 consisting of olivine cumulate gabbro including inverted pigeonite

Abstract: Lunar meteorite Northwest Africa (NWA) 2977 is identified as an olivine cumulate gabbro (OC), consisting of coarse cumulate olivine crystals up to 1 mm with low-Ca and high-Ca pyroxenes, plagioclase, and interstitial incompatible element-rich pockets of K-feldspar, Ca-phosphates, ilmenite, and troilite. These minerals and textures are similar to those of the OC clasts of the NWA 773 clan of meteorites. NWA 2977 contains a variety of pyroxene textures and compositions including augite, pigeonite, and rare ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…Silica minerals are not found in the OG clast. These petrological features are similar to other OG clasts in the NWA 773 clan (Fagan et al 2003;Jolliff et al 2003;Zhang et al 2011;Nagaoka et al 2015;Valencia et al 2019).…”
Section: Petrographysupporting
confidence: 78%
See 2 more Smart Citations
“…Silica minerals are not found in the OG clast. These petrological features are similar to other OG clasts in the NWA 773 clan (Fagan et al 2003;Jolliff et al 2003;Zhang et al 2011;Nagaoka et al 2015;Valencia et al 2019).…”
Section: Petrographysupporting
confidence: 78%
“…The gabbroic lithologies were roughly divided into three types (Fagan et al 2003(Fagan et al , 2014Jolliff et al 2003;Zhang et al 2011;Valencia et al 2019): olivine gabbro (OG, an olivine-pyroxeneplagioclase-rich rock); anorthositic gabbro (AG, a plagioclase-rich rock with some pyroxene); and ferroan gabbro (FG, a group of lithologies all having high Fe# = molar Fe/[Fe + Mg]; see below). OG clasts in NWA 773 clan have been well characterized by previous studies (Fagan et al 2003;Jolliff et al 2003;Zhang et al 2011;Nagaoka et al 2015;Valencia et al 2019). Isotopic Sm-Nd isochron ages of the OG lithology have been analyzed by Borg et al (2009), who reported an age of 2.99 ± 0.03 Ga, and by Nyquist et al (2009), reporting an age of 3.10 ± 0.05 Ga. Isotopic analyses of baddeleyite crystals in the OG lithology and in other types of clasts yield Pb-Pb ages near 3.1 Ga (Zhang et al 2011;Shaulis et al 2017).…”
Section: Methods/experimentalmentioning
confidence: 76%
See 1 more Smart Citation
“…Inverted pigeonite grains in the NWA 2977 OG, found by Nagaoka et al. (), support an origin for the OG as a shallow intrusive magma chamber, as the inversion of pigeonite occurs during slow cooling of plutonic lunar rocks (Papike and Bence ). The size of the chamber need not have been very large and it could have taken the form of a thick sill.…”
Section: Discussionmentioning
confidence: 68%
“…It is inferred to be paired with other lunar meteorites called the NWA 773 clan [4,5], which is a group of paired or petrogenetically related stones that include NWA 773, NWA 2977, NWA 2700, NWA 2727, NWA 3160, NWA 7007, and etc. [6][7][8][9][10][11][12]. In recent years, NWA 773 and its paired meteorites have received extensive attention from planetary chemists because they are significantly different from Apollo and Luna samples and other lunar meteorites [13].…”
Section: Introductionmentioning
confidence: 99%